Economics of Direct Legislation - Matsusaka, J. G. (Quarterly Journal of Economics, 1992)
This paper develops a theory of direct legislation to explain (i) why some issues are resolved by popular vote and others by elected representatives, and (ii) why citizens vote on some ballot propositions and abstain on others. Evidence is provided by a new data set describing 871 California propositions. The main findings are the following. "Good government" issues were usually resolved by legislative measures and distributional issues by initiatives. Citizen-initiated legislation was more common when representatives were unresponsive to the electorate. Voter turnout was higher on distributional propositions than good government propositions. Voter participation on ballot measures has been increasing over time.